THE ROLE OF PARENTS IN INSTILLING MORAL EDUCATION VALUES IN CHILDREN AFTER COVID-19 - Reni Sasmita; Akhsani Sholihati Yasri; Wantini Wantini; Oqy Andaresta (Proceeding International Seminar of Islamic Studies, 2022)
The problem that occurs in post-covid-19 learning is that many students are lazy to do the assignments given by the teacher are not responsible for the assignments given, and also students prefer to play with gadgets to explore social media and play games. This is due to the lack of value education instilled in students both in the school and family environments. This study uses library research methods. The purpose of this study is to describe the very important role of parents in instilling moral education in students after the COVID-19 pandemic. The results in this study are that the role of parents is needed in instilling moral values in students such as respecting concern for others, tolerance, independence, strong will, and also trust and fear God Almighty. This is needed so that students become complete human beings (Insan Kamil). The role of parents and teachers in post-covid-19 learning is to be a role models for children, create a healthy environment in the family, educate and guide them.Keywords: The Role of Parents, Moral Education, After Covid-19